Military Expenditure and Sustainable Economic Growth in Latin America. - Acueva-Jiménez, Maria Gabriel (Journal of Islamic Economy and Community Engagement, 2025)
This research seeks to thoroughly examine the interconnectedness and directional influence between military spending and sustainable economic growth while considering the role of gross fixed capital formation (investment) as a controlling factor. Drawing on a comprehensive dataset from 13 distinct Latin American economies, spanning the extensive time frame of 1990 to 2019, the study investigates the patterns of cointegration and causal relationships within the variables. The results of the cointegration analysis do not provide substantial support for the existence of a strong and enduring relationship between all the examined variables over the long term. Notably, the research identifies a unidirectional causality running from (i) economic growth to military expenditure, (ii) economic growth to investment, and (iii) investment to military expenditure. This suggests a complex interplay between economic dynamics, investment patterns, and military spending behaviors in the context of Latin American economies, highlighting the need for a nuanced understanding of the underlying causal mechanisms at play. Moreover, it is necessary to consider national and international policies to promote sustainable development in countries, given it produces benefits for investment, safety, and security. As nations strive for sustained development, the research underscores the need for policymakers to grapple with the intricate implications of military expenditure on economic and investment landscapes. This holistic perspective advocates for a balanced and inclusive approach, cognizant of the multifaceted challenges and opportunities that characterize the evolving socio-economic and geopolitical landscape of the region.